Low-modulus corrosion-resistant two-component organic silicon sealant as well as preparation method and application thereof
Through the application of low-modulus corrosion-resistant two-component silicone sealant, the problems of prone to cracking and insufficient anti-corrosion performance of anchor concrete in suspension bridge anchoring system are solved, and the synergistic advantages of high elongation and low modulus are achieved, which significantly improves the The life and corrosion resistance of the bridge are achieved.
Patent Information
- Application Number
- CN202411315962.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-10
AI Technical Summary
The existing steel anchoring system is prone to cracking in suspension bridges, and its anti-corrosion performance is insufficient in complex corrosion environments, resulting in the failure of sealant between anchor rods and anchor blocks, affecting the life of the bridge.
Using low-modulus corrosion-resistant two-component silicone sealant, a high elongation and low modulus coating is formed by mixing components A and components B in a specific proportion to form a coating with high elongation and low modulus for isolation between anchor rods and anchor blocks. and anti-corrosion, enhancing tolerance to salt water and high and low temperatures.
The service life of the suspension bridge steel anchoring system is significantly improved, and through the synergistic advantages of high elongation and low modulus, it maintains corrosion resistance and resists performance attenuation after brine immersion and high and low temperature impact.
Smart Images

Figure BDA0005052200620000021 
Figure BDA0005052200620000022 
Figure BDA0005052200620000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of new materials, and in particular to a low-modulus corrosion-resistant two-component organosilicon sealant and a preparation method and application thereof. Background Art
[0002] With the country's strong support for the construction of transportation facilities, the number of cross-river bridges and cross-sea bridges has increased year by year. Among them, the main cables of large-span suspension bridges such as the Ma'anshan Yangtze River Highway Bridge, the Nanjing Yangtze River Fourth Bridge, and the Linyue Expressway Dongting Lake Bridge are applied to the steel anchor system. The steel anchor system is mainly composed of a back beam and an anchor rod. The main cable strand corresponds to the anchor rod, and the entire steel frame is cast in the anchor block concrete. Affected by the gradual increase in the tension of the main cable during the construction process, how to effectively prevent the anchor concrete from cracking under the tension of the anchor rod is a technical problem. At the same time, the steel anchor system faces a complex corrosive environment containing components such as moisture, oxygen, acid, alkali and salt in underground concrete, and the surface of the anchor rod needs to be treated with anti-corrosion.
[0003] In the completed engineering cases of suspension bridge steel anchoring systems, PET foam materials, chloroprene rubber and vulcanized rubber sealants (polysulfide, modified silane) are mainly used to achieve the isolation and corrosion protection of anchor rods and anchor block concrete in the anchoring system. However, PET foam materials have poor waterproof and aging resistance; chloroprene rubber is easily damaged and loses its anti-corrosion function when the anchor rod is stretched under stress; and vulcanized rubber sealants will gradually lose their bonding and anti-corrosion effects on the anchor rod in a long-term humid environment. Summary of the invention
[0004] Based on this, it is necessary to provide a low modulus corrosion-resistant two-component silicone sealant and its preparation method and application. The low modulus corrosion-resistant two-component silicone sealant can be used for the isolation and corrosion protection of anchor rods and anchor block concrete, significantly improving the life of the suspension bridge steel anchoring system.
[0005] The present invention adopts the following technical solution:
[0006] The present invention provides a low modulus corrosion-resistant two-component silicone sealant, comprising a component A and a component B which are mixed in a volume ratio of 10:1 during application;
[0007] The component A is mainly prepared by mixing the following raw materials in parts by weight: 100 parts of α,ω-dihydroxy polydimethoxysiloxane, 30-100 parts of dimethyl silicone oil, 50-150 parts of active nano calcium carbonate, and 10-80 parts of active heavy calcium carbonate whose surface is treated with fatty acid substances;
[0008] The B component is mainly prepared by mixing the following raw materials in parts by weight: 100 parts of reinforcing filler, 280-380 parts of dimethyl silicone oil, 100-250 parts of cross-linked tackifier, and 0.1-1 part of catalyst; and the cross-linked tackifier is prepared by reacting alkoxysilane, alkoxysilane oligomer, aminosilane and epoxy silane at 110°C-120°C under inert atmosphere conditions and removing small molecular substances by atmospheric distillation.
[0009] In some embodiments, the weight ratio of alkoxysilane, alkoxysilane oligomer, aminosilane and epoxysilane is (1.5-1.8):(3-3.5):(2.5-2.8):(0.8-1).
[0010] In some embodiments, the alkoxysilane is selected from R1Si(OR2)3, and R1 is selected from methyl, ethyl or vinyl, and R2 is methyl or ethyl;
[0011] The alkoxysilane oligomer is selected from the compounds of the following structures:
[0012]
[0013] Furthermore, R3 is a methyl group or an ethyl group, and n is 2 to 10;
[0014] The aminosilane is selected from R4 NH(CH2)3Si(OR5)3, and R4 is selected from hydrogen or phenyl, and R5 is selected from methyl or ethyl;
[0015] The epoxy silane is selected from the compounds selected from the following structures:
[0016]
[0017] And R6 is selected from methyl or ethyl.
[0018] In some embodiments, the viscosity of α,ω-dihydroxypolydimethoxysiloxane at 25±1° C. is in the range of 50,000 to 200,000 mPa·s, preferably in the range of 70,000 to 120,000 mPa·s, and more preferably in the range of 80,000 to 100,000 mPa·s.
[0019] In some embodiments, the viscosity of the dimethyl silicone oil at 25±1° C. ranges from 1000 to 20000 mPa·s, preferably from 8000 to 15000 mPa·s.
[0020] In some embodiments, the BET specific surface area of active nano calcium carbonate is 10 to 18 m 2 / g, activation rate 100%.
[0021] In some of the embodiments, the D50 particle size of the activated heavy calcium carbonate after the surface is treated with fatty acid substances is less than 7 μm, and the activation rate is 100%.
[0022] In some of the embodiments, the A component is mainly prepared by mixing the following raw materials in parts by weight: 100 parts of α, ω-dihydroxy polydimethoxysiloxane, 50-80 parts of dimethyl silicone oil, 70-140 parts of active nano calcium carbonate, and 20-80 parts of active heavy calcium carbonate whose surface is treated with fatty acids; the B component is mainly prepared by mixing the following raw materials in parts by weight: 100 parts of carbon black, 300-350 parts of dimethyl silicone oil, 120-150 parts of cross-linked tackifier, and 0.3-0.6 parts of catalyst.
[0023] In some embodiments, the reinforcing filler is selected from carbon black or fumed silica.
[0024] The present invention also provides a method for preparing the low modulus corrosion-resistant two-component silicone sealant, comprising the following steps:
[0025] Preparation of component A: adding α,ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, active nano calcium carbonate and active heavy calcium carbonate into a double planetary power mixer and dispersing them evenly to obtain component A;
[0026] Preparation of component B: Add reinforcing filler and dimethyl silicone oil into a double planetary power mixer, stir, evacuate and stir, and heat to 100°C for dehydration; after reducing the temperature in the mixer to below 50°C, gradually add cross-linking tackifier and catalyst under nitrogen protection, stir evenly under vacuum, fill with nitrogen to release the vacuum to normal pressure, and obtain component B.
[0027] The present invention also provides application of the low modulus corrosion-resistant two-component organic silicon sealant in a bridge steel anchoring system.
[0028] Compared with the prior art, the core advantages of the present invention are:
[0029] The low modulus corrosion-resistant two-component silicone sealant of the present invention is prepared by compounding various raw materials in specific proportions to prepare component A and component B. When applied to anchor rods, the coating formed by mixing component A and component B can have a modulus of less than 0.3 MPa at 23°C and 100% elongation, and an elongation at break of more than 600%. The performance degradation is not obvious after being soaked in salt water and subjected to high and low temperature shocks, thereby meeting the application requirements of anti-corrosion of anchor rods in bridge steel anchoring systems and isolation from concrete, and has good corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] None. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly. The following embodiments are only used to illustrate the present invention, but are not only used to limit the scope of the present invention. Based on the specific embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work belong to the protection scope of the present invention. In the embodiments of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the embodiments of the present invention, if not specifically specified, the technical means used are conventional means well known to those skilled in the art.
[0032] Sources and physical and chemical properties of key materials:
[0033] α, ω-dihydroxypolydimethoxysiloxane: viscosity 80000 mPa·s, 100000 mPa·s, purchased from Jiangxi Lanxing Xinghuo Silicone Co., Ltd.
[0034] Dimethyl silicone oil: viscosity 8000mPa·s, 10000mPa·s, 12500mPa·s, purchased from Jiangxi Lanxing Xinghuo Silicone Co., Ltd.
[0035] Active nanocarbonate: specific surface area 15±3m 2 / g, activation rate 100%, purchased from Guangxi Huana New Materials Co., Ltd.
[0036] Active heavy calcium carbonate: particle size D97 is less than 5μm, surface treated with fatty acid substances, activation rate 100%, purchased from Jiangxi Guangyuan Chemical Co., Ltd.
[0037] Methyltrimethoxysilane, ethyltrimethoxysilane, polymethyltriethoxysilane, aminopropyltriethoxysilane, aminophenylpropyltrimethoxysilane, and 3-glycidyloxypropyltrimethoxysilane were purchased from Hubei Jianghan New Materials Co., Ltd.
[0038] The following example illustrates this.
[0039] Test Example 1-1
[0040] This test example provides a cross-linked tackifier, and the preparation method thereof is as follows: 150 g of methyltrimethoxysilane, 350 g of polymethyltriethoxysilane, 250 g of aminopropyltriethoxysilane and 80 g of 3-glycidyloxypropyltrimethoxysilane are added to an anhydrous dry flask with a reflux device, nitrogen is introduced into the flask, heating is turned on, the temperature is raised to 110°C to 120°C and kept warm for 8 hours, and an A1 cross-linked tackifier is obtained.
[0041] Test Example 1-2
[0042] This test example provides a cross-linked tackifier, and its preparation method includes: adding 180g of ethyltrimethoxysilane, 300g of polymethyltriethoxysilane, 280g of aminophenylpropyltrimethoxysilane and 100g of 3-glycidyloxypropyltriethoxysilane into an anhydrous dry flask with a reflux device, passing nitrogen into the flask, turning on the heating, raising the temperature to 110°C-120°C and keeping it warm for 8h to obtain A2 cross-linked tackifier.
[0043] Test Example 1-3
[0044] This test example provides a cross-linked tackifier, and its preparation method includes: adding 480 g of ethyltrimethoxysilane, 280 g of aminophenylpropyltrimethoxysilane and 100 g of 3-glycidyloxypropyltriethoxysilane into an anhydrous dry flask with a reflux device, passing nitrogen into the flask, turning on the heating, raising the temperature to 110°C-120°C and keeping it warm for 8 hours to obtain A3 cross-linked tackifier.
[0045] Test Examples 1-4
[0046] This test example provides a cross-linked tackifier, and its preparation method includes: adding 180 g of ethyltrimethoxysilane, 300 g of polymethyltriethoxysilane, and 280 g of aminophenylpropyltrimethoxysilane into an anhydrous dry flask with a reflux device, passing nitrogen into the flask, turning on the heating, raising the temperature to 110°C-120°C and keeping it warm for 8 hours to obtain A4 cross-linked tackifier.
[0047] Test Example 2-1
[0048] This test example provides a two-component silicone sealant, including component A and component B.
[0049] Component A uses the following raw materials in parts by weight: 100 parts of 80000 mPa·s α, ω-dihydroxy polydimethoxysiloxane, 60 parts of 10000 mPa·s dimethyl silicone oil, 100 parts of active nano calcium carbonate, and 40 parts of active heavy calcium carbonate.
[0050] Component B uses the following raw materials in parts by weight: 100 parts of reinforcing filler carbon black, 320 parts of 10000 mPa·s dimethyl silicone oil, 150 parts of A1 cross-linking tackifier, and 0.5 parts of catalyst dibutyl tin dilaurate.
[0051] The preparation method of the two-component silicone sealant in this test example is as follows:
[0052] Preparation of component A: Add α,ω-dihydroxypolydimethoxysiloxane, dimethyl silicone oil, active nano calcium carbonate, and active heavy calcium carbonate into a power mixer, and disperse for 30 minutes at a temperature below 45° C. and a vacuum degree of -0.096 MPa to obtain component A.
[0053] Preparation of component B: Add carbon black and dimethyl silicone oil into a double planetary power mixer and stir. After 0.5 h, vacuum stir and heat to 100°C for dehydration for 2 h. After reducing the temperature in the mixer to below 50°C, gradually add A1 cross-linking thickener and catalyst dibutyl tin dilaurate under nitrogen protection, stir evenly under vacuum, and release the vacuum to normal pressure with nitrogen to obtain component B.
[0054] When used, component A and component B are mixed evenly in a volume ratio of 10:1 to obtain a two-component silicone sealant coating. Tests show that the surface drying time of the coating is 90 minutes.
[0055] Test Example 2-2
[0056] This test example provides a two-component silicone sealant, including component A and component B.
[0057] Component A uses the following raw materials in parts by weight: 100 parts of 100000 mPa·s α, ω-dihydroxy polydimethoxysiloxane, 80 parts of 8000 mPa·s dimethyl silicone oil, 80 parts of active nano calcium carbonate, and 80 parts of active heavy calcium carbonate.
[0058] Component B uses the following raw materials in parts by weight: 100 parts of carbon black, 350 parts of 10000 mPa·s dimethyl silicone oil, 120 parts of A1 cross-linking tackifier, and 0.5 parts of dibutyl tin dilaurate.
[0059] The preparation method of the two-component silicone sealant in this test example is the same as that of Test Example 2-1.
[0060] When used, component A and component B are evenly mixed in a volume ratio of 10:1 to obtain a two-component silicone sealant coating. Tests show that the surface drying time of the coating is 100 minutes.
[0061] Test Example 2-3
[0062] This test example provides a two-component silicone sealant, including component A and component B.
[0063] Component A uses the following raw materials in parts by weight: 100 parts of 80000 mPa·s α, ω-dihydroxy polydimethoxysiloxane, 60 parts of 10000 mPa·s dimethyl silicone oil, 100 parts of active nano calcium carbonate, and 40 parts of active heavy calcium carbonate.
[0064] Component B uses the following raw materials in parts by weight: 100 parts of carbon black, 320 parts of 10000 mPa·s dimethyl silicone oil, 150 parts of A2 cross-linking tackifier, and 0.5 parts of dibutyl tin dilaurate.
[0065] The preparation method of the two-component silicone sealant in this test example is the same as that of Test Example 2-1.
[0066] When used, component A and component B are mixed evenly in a volume ratio of 10:1 to obtain a two-component silicone sealant coating. Tests show that the surface drying time of the coating is 95 minutes.
[0067] Test Example 2-4
[0068] This test example provides a two-component silicone sealant, including component A and component B.
[0069] Component A uses the following raw materials in parts by weight: 50 parts of 80000mPa·s α, ω-dihydroxy polydimethoxysiloxane, 50 parts of 100000mPa·s α, ω-dihydroxy polydimethoxysiloxane, 60 parts of 10000mPa·s dimethyl silicone oil, 140 parts of active nano calcium carbonate, and 20 parts of active heavy calcium carbonate.
[0070] Component B uses the following raw materials in parts by weight: 100 parts of carbon black, 320 parts of 10000 mPa·s dimethyl silicone oil, 120 parts of A2 cross-linking tackifier, and 0.5 parts of dibutyl tin dilaurate.
[0071] The preparation method of the two-component silicone sealant in this test example is the same as that of Test Example 2-1.
[0072] When used, component A and component B are evenly mixed in a volume ratio of 10:1 to obtain a two-component silicone sealant coating. Tests show that the surface drying time of the coating is 110 minutes.
[0073] Test Example 2-5
[0074] This test example provides a two-component silicone sealant, including component A and component B.
[0075] Component A uses the following raw materials in parts by weight: 100 parts of 100000 mPa·s α, ω-dihydroxy polydimethoxysiloxane, 60 parts of 12500 mPa·s dimethyl silicone oil, 70 parts of active nano calcium carbonate, and 50 parts of active heavy calcium carbonate.
[0076] Component B uses the following raw materials in parts by weight: 100 parts of carbon black, 320 parts of 12500 mPa·s dimethyl silicone oil, 120 parts of A2 cross-linking tackifier, and 0.5 parts of dibutyl tin dilaurate.
[0077] The preparation method of the two-component silicone sealant in this test example is the same as that of Test Example 2-1.
[0078] When used, component A and component B are evenly mixed in a volume ratio of 10:1 to obtain a two-component silicone sealant coating. Tests show that the surface drying time of the coating is 100 minutes.
[0079] Comparative Example 3-1
[0080] This comparative test example provides a two-component silicone sealant, whose raw material components are basically the same as those of Test Example 2-1, with the only difference being that the active heavy calcium carbonate in the raw material of component A is replaced with heavy calcium carbonate whose surface is not activated by fatty acid.
[0081] Comparative Example 3-2
[0082] This comparative test example provides a two-component silicone sealant, including component A and component B.
[0083] Component A and its preparation method are the same as those in Test Example 2-1.
[0084] Component B and its preparation method are different from those in Test Example 2-1, specifically in that A-1 cross-linking tackifier is not directly used. Instead, 100 parts of carbon black and 320 parts of 10,000 mPa·s dimethyl silicone oil are added to a double planetary power mixer, stirred for 0.5 h, vacuum stirred and heated to 100°C for dehydration for 2 h; after the temperature in the mixer kettle is reduced to below 50°C, 27.1 parts of methyltrimethoxysilane, 63.25 parts of polymethyltriethoxysilane, 45.2 parts of aminopropyltriethoxysilane, 14.46 parts of 3-glycidyloxypropyltrimethoxysilane and 0.5 parts of dibutyltin dilaurate are added respectively under nitrogen filling conditions, stirred evenly under vacuum filling conditions, and the vacuum is released to normal pressure by nitrogen filling to obtain component B.
[0085] Comparative Example 3-3
[0086] This comparative test example provides a two-component silicone sealant, whose raw material components are basically the same as those of Test Example 2-1, and the only difference is that the A1 cross-linked tackifier in the raw material of component A is replaced by an A3 cross-linked tackifier.
[0087] Comparative Example 3-4
[0088] This comparative test example provides a two-component silicone sealant, whose raw material components are basically the same as those of Test Example 2-1, and the only difference is that the A1 cross-linked tackifier in the raw material of component A is replaced by an A4 cross-linked tackifier.
[0089] The raw materials and dosage of two-component silicone sealants are summarized in the following table:
[0090] Statistics of raw material usage of component A
[0091]
[0092] Statistics of raw material usage of component B
[0093]
[0094] The two-component silicone sealants prepared in the above experiments were tested for performance according to specific test standards:
[0095] (1)Tensile strength & elongation at break shall be tested in accordance with GB / T 528 test standard.
[0096] (2) Tensile modulus at 100% elongation, refer to JC / T 976-2005 test standard.
[0097] (3) 180° peel strength, refer to HB 5249 test standard.
[0098] (4) Bonding material: Anchor metal material, with epoxy primer applied on the surface.
[0099] The two-component silicone sealant prepared in the above experiment was used to prepare coating test samples, which were immersed in a (23±2)°C, 5wt% sodium chloride aqueous solution for aging and aged in a high and low temperature cycle test box at -20°C to 90°C.
[0100] The performance test results are shown in the following table:
[0101]
[0102]
[0103] From the test results in the above table, we can see that:
[0104] The elastic modulus of the two-component silicone sealant prepared in the above test examples 2-1 to 2-5 is less than 0.3MPa, the elongation at break is greater than 600%, the performance is maintained well after being soaked in salt water and subjected to high and low temperature shock, and the surface adhesion performance to the protective material is maintained well. The two-component silicone sealant prepared in the above experimental examples has the synergistic advantages of high elongation, low modulus and strength, and can provide long-term corrosion protection for the bridge anchor system.
[0105] The application test results of comparative example 3-1 show that after being immersed in water and subjected to high and low temperature shock, the performance decays significantly.
[0106] The application test results of Comparative Example 3-2 show that the cross-linking agent and tackifier of component B are not oligomerized, and the performance of the finished product is significantly degraded after being immersed in water.
[0107] The application test results of Comparative Examples 3-3 and 3-4 show that the lack of specific ingredients in the cross-linked tackifier in component B has a significant impact on the performance of the finished product (especially the synergistic performance of elongation and modulus).
[0108] It is necessary to point out that the above embodiments are limited to further elaboration and explanation of the technical solution of the present invention, and are not further limitations of the technical solution of the present invention. The method of the present invention is only a preferred implementation scheme, and is not used to limit the protection scope of the present invention. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low modulus corrosion-resistant two-component silicone sealant, characterized in that: It includes component A and component B which are mixed in a volume ratio of 10:1 during application; The component A is mainly prepared by mixing the following raw materials in parts by weight: 100 parts of α,ω-dihydroxy polydimethoxysiloxane, 30-100 parts of dimethyl silicone oil, 50-150 parts of active nano calcium carbonate, and 10-80 parts of active heavy calcium carbonate whose surface is treated with fatty acid substances; The B component is mainly prepared by mixing the following raw materials in parts by weight: 100 parts of reinforcing filler, 280-380 parts of dimethyl silicone oil, 100-250 parts of cross-linked tackifier, and 0.1-1 part of catalyst; and the cross-linked tackifier is prepared by reacting alkoxysilane, alkoxysilane oligomer, aminosilane and epoxy silane at 110°C-120°C under inert atmosphere conditions and removing small molecular substances by atmospheric distillation.
2. The low modulus corrosion-resistant two-component silicone sealant according to claim 1, characterized in that: The weight ratio of alkoxysilane, alkoxysilane oligomer, aminosilane and epoxysilane is (1.5-1.8):(3-3.5):(2.5-2.8):(0.8-1).
3. The low modulus corrosion-resistant two-component silicone sealant according to claim 2, characterized in that: The alkoxysilane is selected from R1Si(OR2)3, and R1 is selected from methyl, ethyl or vinyl, and R2 is methyl or ethyl; The alkoxysilane oligomer is selected from the compounds of the following structures: Furthermore, R3 is a methyl group or an ethyl group, and n is 2 to 10; The aminosilane is selected from R4 NH(CH2)3Si(OR5)3, and R4 is selected from hydrogen or phenyl, and R5 is selected from methyl or ethyl; The epoxy silane is selected from the following compounds: And R6 is selected from methyl or ethyl.
4. The low modulus corrosion-resistant two-component silicone sealant according to any one of claims 1 to 3, characterized in that: The viscosity of α,ω-dihydroxypolydimethoxysiloxane at 25±1°C is in the range of 50000 to 200000 mPa·s.
5. The low modulus corrosion-resistant two-component silicone sealant according to any one of claims 1 to 3, characterized in that: The viscosity of dimethyl silicone oil at 25±1℃ ranges from 1000 to 20000 mPa·s.
6. The low modulus corrosion-resistant two-component silicone sealant according to any one of claims 1 to 3, characterized in that: The BET specific surface area of active nano calcium carbonate is 10-18 m 2 / g, activation rate 100%; The D50 particle size of the activated heavy calcium carbonate treated with fatty acid substances is less than 7 μm, and the activation rate is 100%.
7. The low modulus corrosion-resistant two-component silicone sealant according to any one of claims 1 to 3, characterized in that: The component A is mainly prepared by mixing the following raw materials in parts by weight: 100 parts of α,ω-dihydroxy polydimethoxysiloxane, 50-80 parts of dimethyl silicone oil, 70-140 parts of active nano calcium carbonate, and 20-80 parts of active heavy calcium carbonate whose surface is treated with fatty acid substances; The B component is mainly prepared by mixing the following raw materials in parts by weight: 100 parts of carbon black, 300-350 parts of dimethyl silicone oil, 120-150 parts of a cross-linking tackifier, and 0.3-0.6 parts of a catalyst.
8. The low modulus corrosion-resistant two-component silicone sealant according to any one of claims 1 to 3, characterized in that: The reinforcing filler is selected from carbon black or fumed silica.
9. The method for preparing the low modulus corrosion-resistant two-component silicone sealant according to any one of claims 1 to 8, characterized in that: The steps include: Preparation of component A: adding α,ω-dihydroxy polydimethylsiloxane, dimethyl silicone oil, active nano calcium carbonate and active heavy calcium carbonate into a double planetary power mixer and dispersing them evenly to obtain component A; Preparation of component B: Add reinforcing filler and dimethyl silicone oil into a double planetary power mixer, stir, evacuate and stir, and heat to 100°C for dehydration; after reducing the temperature in the mixer to below 50°C, gradually add cross-linking tackifier and catalyst under nitrogen protection, stir evenly under vacuum, fill with nitrogen to release the vacuum to normal pressure, and obtain component B.
10. Use of the low modulus corrosion-resistant two-component silicone sealant according to any one of claims 1 to 8 in a bridge steel anchoring system.